Ilusão fiscal, cidadania e tributação do consumo em reforma: a (in)consciência do contribuinte antes, durante e depois (?) da emenda constitucional n. 132/2023 e da lei complementar n. 214/2025 (reforma tributária) - Cunha, Isaac Rodrigues (2025)
The tax reform ushered by Constitutional Amendment No. 132/2023 and partially implemented through Complementary Law No. 214/2025 has profoundly reshaped Brazil’s tax framework, particularly in the sphere of consumption levies. Far from enjoying meaningful public participation, the reform reflects the widespread apathy that historically surrounds so‑called indirect taxation. Within this context, the study examines the phenomenon of fiscal illusion – a theory formulated by Amilcare Puviani (1903) that denotes citizens’ estrangement from, and ignorance of, fiscal realities, regarded alternately as an unintended side effect and as a purposeful tool of domination. Building on this premise, the inquiry investigates how consumption taxes may reinforce, rather than reduce, social inequalities when “illusioned” taxpayers lack any real understanding of the State’s fiscal activity and, consequently, do not engage with it. The analysis traces the evolution of consumption and consumer relations from the earliest chapters of global economic history to their current manifestations in the digital economy, with special attention to the post‑COVID‑19 period of acute economic crisis whose effects still resonate. It also explores how the structure and regressivity of consumption taxation have changed—and will continue to change once the vacatio legis stipulated by the amendment expires—and whether the fiscal illusion has been mitigated by the long‑awaited reform. Methodologically, the research combines bibliographic and documentary approaches, consulting books, book chapters, and peer‑reviewed journal articles alongside primary documentary sources; it is therefore classified as pure, qualitative, descriptive, and exploratory. The findings show that fiscal illusion, as conceptualized by Puviani, persists precisely in an environment of widespread misinformation; the dispersion of indirect taxes through consumption levies, despite the simplification promoted by the reform, continues to hamper taxpayers’ awareness of the amounts transferred to the State; new mechanisms such as the cashback scheme created by the reform and detailed in Complementary Law No. 214/2025 coupled with information duties under article 150, § 5 of the Federal Constitution and article 6 III of the Consumer Protection Code - can both ease the burden of economic incidence and foster greater taxpayer awareness. Consumption taxation is thus not the whole problem but part of it - and also part of its solution - especially given new consumption patterns that harm consumers, the economy, and the environment. Accordingly, consumption taxes require not only a rethinking of their traditional fiscal‑revenue paradigm but also an overdue update of their extrafiscal function to discourage - since outright prohibition is impossible - (hyper)consumption that is (hyper)harmful to public health and to the planet.